2022
DOI: 10.3390/nu14061166
|View full text |Cite
|
Sign up to set email alerts
|

Mild Endurance Exercise during Fasting Increases Gastrocnemius Muscle and Prefrontal Cortex Thyroid Hormone Levels through Differential BHB and BCAA-Mediated BDNF-mTOR Signaling in Rats

Abstract: Mild endurance exercise has been shown to compensate for declined muscle quality and may positively affect the brain under conditions of energy restriction. Whether this involves brain-derived neurotrophic factor (BDNF) and mammalian target of rapamycin (mTOR) activation in relation to central and peripheral tissue levels of associated factors such as beta hydroxy butyrate (BHB), branched-chain amino acids (BCAA) and thyroid hormone (T3) has not been studied. Thus, a subset of male Wistar rats housed at thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…At the molecular level, metabolic flexibility relies on the configuration of signaling pathways that manage nutrient sensing, uptake, transport, storage, and utilization. In cultured C2C12 myotubes, BDNF secretion was provoked by the biochemical factors of fasting, including glucose depletion, amino acid restriction, and β-hydroxybutyrate (βHB) stimulation [ 28 , 60 , 80 , 81 ]. We and others have also shown that Bdnf expression in Skm is increased during fasting, suggesting mBDNF might be involved in regulating metabolism to move through the fed-fast cycle [ 60 , 81 ].…”
Section: Bdnf In Skeletal Musclementioning
confidence: 99%
See 4 more Smart Citations
“…At the molecular level, metabolic flexibility relies on the configuration of signaling pathways that manage nutrient sensing, uptake, transport, storage, and utilization. In cultured C2C12 myotubes, BDNF secretion was provoked by the biochemical factors of fasting, including glucose depletion, amino acid restriction, and β-hydroxybutyrate (βHB) stimulation [ 28 , 60 , 80 , 81 ]. We and others have also shown that Bdnf expression in Skm is increased during fasting, suggesting mBDNF might be involved in regulating metabolism to move through the fed-fast cycle [ 60 , 81 ].…”
Section: Bdnf In Skeletal Musclementioning
confidence: 99%
“…In cultured C2C12 myotubes, BDNF secretion was provoked by the biochemical factors of fasting, including glucose depletion, amino acid restriction, and β-hydroxybutyrate (βHB) stimulation [ 28 , 60 , 80 , 81 ]. We and others have also shown that Bdnf expression in Skm is increased during fasting, suggesting mBDNF might be involved in regulating metabolism to move through the fed-fast cycle [ 60 , 81 ]. Giacco et al further demonstrated that fasting-induced Bdnf expression is associated with elevated phosphorylation of cAMP-responsive element-binding protein (CREB), TrkB, and AMPK in the skeletal muscle [ 81 ].…”
Section: Bdnf In Skeletal Musclementioning
confidence: 99%
See 3 more Smart Citations